Synthesis of covalent organic frameworks using sustainable solvents and machine learning. Issue 22 (22nd October 2021) - Kumar, Sushil; Ignacz, Gergo; Szekely, Gyorgy
Abstract : Covalent organic frameworks have been prepared in sustainable solvents by a solvothermal method, and their porosity and crystallinity were predicted using QSPR and machine learning approaches. Abstract : Covalent organic frameworks (COFs) have attracted considerable interest owing to their structural predesign ability, controllable chemistry, long-range periodicity, and pore interior functionalization ability. The most widely adopted solvothermal synthesis of COFs requires the use of toxic organic solvents. In line with the 5 th principle of green chemistry and the United Nations' 12 th Sustainable Development Goal, we aim to mitigate the adverse effect of solvents on COF synthesis. Here we have investigated twelve green solvents for the sustainable synthesis of five series of COFs using the solvothermal approach. Crystallinity and porosity were used to assess the quality of the obtained COFs. In addition, the suitability of the solvents in the synthesis of crystalline and porous COFs was investigated and color-coded for the final green assessment. In particular, γ-butyrolactone (for TpPa, TpBD, and TpAzo ), para -cymene (TpAnq ), and PolarClean (TpTab ) were found to be excellent green solvents to produce high-quality COFs. For the first time, we successfully used quantitative structure–property relationships in combination with machine learning approaches to predict both the surface area and crystallinity of COFs using the structure of the solvents and COF building blocks.